MESH360: a framework for designing MMR-enhanced clinical simulations - Thomas Cochrane; Stephen Aiello; Stuart Cook; Claudio Aguayo; Norm Wilkinson (Association for Learning Technology, 2020)
This article evaluates the results of two prototype iterations of a design-based research project that explores the application of mobile mixed reality (MMR) to enhance critical care clinical health education simulation in Paramedicine. The project utilises MMR to introduce critical elements of patient and practitioner risk and stress into clinical simulation learning scenarios to create more authentic learning environments. Subjective participant feedback is triangulated against participant biometric data to validate the level of participant stress introduced to clinical simulation through the addition of MMR. Results show a positive impact on the learning experience for both novice and professional paramedic practitioners. The article highlights the development of implementation and data triangulation methodologies that can be utilised to enhance wider clinical simulation contexts than the original context of Paramedicine education. We argue that our collaborative transdisciplinary design team model provides a transferable framework for designing MMR-enhanced clinical simulation environments.